Pertimbangan Mahkamah Agung Memutus Penuntutan Tidak Dapat Diterima (Nebis In Idem) Dalam Perkara Pembunuhan - Krisna Vidya Antakusuma (Sebelas Maret University, 2019)
This research aims is to fnd out the reconsideration by defendant on the basis of a failure to apply the judge, judex facti and oversight in deciding cases of murder . This research includes studies of normative prescriptive. The case studied in this study were cases of murder that committed by the convict named Sri Suprihatin and Sri Handoko which occurred in 2013, that can be seen on the Supreme Court Decision Number. 57/PK/PID/2015. Based on the research, this study obtain result that the reconsideration proposed by the defendant with judex facti reason. This is indicated by the principle of nebis in idem has fulflled contained in Article 263 paragraph 2 letter c of KUHAP about prerequirement to propose reconsideration appeal. The decision have shown an oversight of the Judge or a decision of judex factie’s apparent verdict in the murder case, with the result that the Supreme Court’s decision granted the request of reconsideration, and canceled the decision of the District Court Number 719/Pid.B/2013/PN.Smg on the 5th of February 2014, prosecute and declare that the Prosecutor’s claim to the convict Sri Handoko is unacceptable because of nebis in idem.Keywords : Murder, Reconsideration, Nebis In Idem